Refractory sagger for calcining precursor material

By forming a high-content spinel protective layer on the inner surface of the refractory silt and optimizing the composition of ceramic materials, the damage and cracks of the refractory silt caused by side reactions between lithium raw materials and ceramic materials is solved, and the refractory and service life are achieved. promote.

CN119325460APending Publication Date: 2025-01-17ECOPRO BM CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202380045435.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-10-19
Filing Date
2023-05-30
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

During the calcination of inorganic compound precursor materials, the by-products are produced by the side reaction between lithium raw materials and ceramic materials, resulting in damage to the inner wall of the refractory silhouette, reduced strength and shortened service life, and the volume changes at high temperatures cause cracks. The problem.

Method used

The protective layer with at least 50% spinel content is formed on the inner surface of the refractory silt silt bowl, and a dense structure is formed to reduce the lithium raw material by reasonably adjusting the composition and structure of the ceramic material, including the particle size distribution and proportion of the master batch and aggregate. Permeation and reaction, improve refraction resistance and peel resistance.

Benefits of technology

It effectively reduces the generation of by-products, extends the service life of the refractory silhouette, improves its heat resistance and crack resistance, and ensures stable operation under high temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005174084710000171
    Figure BDA0005174084710000171
  • Figure BDA0005174084710000181
    Figure BDA0005174084710000181
  • Figure BDA0005174084710000182
    Figure BDA0005174084710000182
Patent Text Reader

Abstract

The present invention relates to a refractory sagger for calcining a precursor material, and more particularly, to a refractory sagger provided with a space for loading a precursor material inside, which can improve the durability of a main body while suppressing the generation of by-products when calcining a precursor material using the refractory sagger.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a refractory sagger for calcining precursor materials, and more particularly to a refractory sagger having a space for loading precursor materials inside, which can suppress the generation of by-products when calcining precursor materials using the refractory sagger and improve the durability of the main body. Background Art

[0002] Various inorganic compounds are prepared by heat treatment (calcination) of precursor materials.

[0003] Generally, calcination of a precursor material of an inorganic compound is achieved by placing the precursor material in a heat treatment container having heat resistance and chemical resistance (hereinafter referred to as a "refractory sagger") and performing a heat treatment at a predetermined temperature.

[0004] At this time, since the precursor material of the compound to be heat-treated (inorganic compound or its raw material) is placed inside the refractory sagger, it is calcined by heating without being directly exposed to flame, smoke, and the like.

[0005] Therefore, the refractory sagger must basically ensure stability at the calcination temperature of the precursor material, that is, predetermined heat resistance and chemical resistance.

[0006] A representative example of an inorganic compound prepared by heat treatment of a precursor material is a positive electrode active material for a lithium battery.

[0007] Compounds used as positive electrode active materials for lithium batteries include lithium nickel oxide, lithium cobalt oxide, lithium manganese oxide, or composite oxides thereof (eg, NCM, NCA-based lithium composite oxides), and the like.

[0008] In the case of the positive electrode active material, a transition metal-containing precursor material and a lithium-containing raw material (eg, LiOH) are loaded into a refractory sagger and then heat-treated at a temperature of 600° C. to 1,200° C. to prepare.

[0009] Therefore, the refractory sagger used for preparing the positive electrode active material is prepared using high heat-resistant ceramic materials such as cordierite, mullite, spinel, etc. as the main component to ensure sufficient heat resistance within the above-mentioned heat treatment temperature range.

[0010] On the other hand, in recent years, attention has been paid to the problem of byproducts generated in the refractory sagger due to a side reaction (see the following reaction formula) between the lithium-containing raw material and the main component of the refractory sagger at the heat treatment temperature of the precursor material.

[0011] Specifically, lithium contained in lithium-containing raw materials such as LiOH and Li2CO3 added to the refractory sagger for calcination of precursor materials penetrates into the refractory sagger during the calcination process, and may react with Al2O3, SiO2, etc., which are main components of the refractory sagger.

[0012] By the infiltration and reaction of lithium as described above, Li x -(Al / Si) y -O z By-products of etc.

[0013] According to the above mechanism, as the calcination process using the above refractory sagger is repeated, the thickness of the by-product layer deposited on the above refractory sagger increases.

[0014] Since the by-product layer is generated on the inner wall of the refractory sagger, the inner wall of the refractory sagger is damaged, which may shorten the strength and life of the refractory sagger.

[0015] In addition, the by-product layer may cause a problem of being separated and mixed into the positive electrode active material during calcination due to a difference in thermal expansion coefficient with the refractory sagger.

[0016] To improve this, technologies have been introduced to reduce the possibility of by-product generation by excluding silicon-containing raw materials from the main components of the refractory sagger, or to reduce the side reaction between the refractory sagger and the lithium-containing raw material by coating the inner wall of the refractory sagger with spinel or the like.

[0017] However, when the silicon-containing raw material in the main component of the refractory sagger is reduced, the content of the aluminum-containing raw material must be increased. In this case, there is a problem that the possibility of generating by-products derived from aluminum instead of by-products derived from silicon increases, and there is also a problem that the overall strength of the refractory sagger is reduced due to the exclusion or reduction of the silicon-containing raw material in the main component of the refractory sagger.

[0018] Furthermore, in addition to the problems caused by peeling, due to the repeated exposure of the sagger at high temperatures, its volume changes with temperature, and the accumulated stress can cause cracks in the sagger, thereby reducing the service life characteristics.

[0019] [Prior art literature]

[0020] [Patent Document]

[0021] (Patent Document 1) Korean Patent Publication No. 10-2020-0058383 (Publication Date: 2020.05.27)

[0022] (Patent Document 2) Korean Patent Gazette No. 10-1161139 (Published on July 2, 2012)

[0023] (Patent Document 3) Korean Patent Publication No. 10-1448417 (Publication Date: 2014.10.07) Summary of the invention

[0024] Technical issues

[0025] An object of the present specification is to provide a refractory sagger having sufficient heat resistance under temperature conditions applied during calcination of a precursor material of an inorganic compound.

[0026] In addition, another object of the present specification is to provide a refractory sagger, which, unlike the existing refractory sagger, can prevent the generation of lithium-containing raw materials such as Li by reducing the side reaction between the lithium-containing raw materials loaded into the refractory sagger and the main components of the refractory sagger. x -(Al / Si) y -O z By-products of etc.

[0027] In addition, another object of the present specification is to provide a refractory sagger having sufficient strength to effectively withstand the pressure or high temperature calcination conditions applied to the inner wall of the refractory sagger when the precursor material is loaded into the sagger and then pressed.

[0028] In addition, another object of the present specification is to provide a refractory sagger that can solve the problem of cracks caused by stress caused by volume changes of the refractory sagger itself.

[0029] The purpose of the present invention is not limited to the purpose mentioned above, and other purposes and advantages of the present invention not mentioned can be understood through the following description, and can be more clearly understood through the embodiments of the present invention. In addition, it can be easily understood that the purpose and advantages of the present invention can be achieved by the means and combinations thereof in the claims.

[0030] Solutions to the problem

[0031] According to one aspect of the present invention, a refractory sagger for calcining precursor materials is provided, which is a refractory sagger having a space for loading the precursor materials on the inside, and a protective layer having a spinel content of more than 50 wt% is formed on at least a portion of the inner surface of the refractory sagger for loading the precursor materials.

[0032] In one embodiment, the protective layer may further include at least one selected from the group consisting of corundum, mullite, petalite, spodumene, cordierite, quartz and zircon.

[0033] As one of several examples, the corundum content of the protective layer may be 25 wt % or less.

[0034] In another example, the protective layer may be a spinel continuous phase masterbatch matrix in which a discontinuous phase aggregate including at least one selected from the group consisting of corundum, mullite, petalite, spodumene, cordierite, quartz and zircon is dispersed.

[0035] At this time, the average particle size of the spinel masterbatch may be 0.5 μm to 25 μm, and the average particle size of the aggregate may be 150 μm to 900 μm.

[0036] In one embodiment, the thickness of the protective layer may be 2.5 mm to 4.0 mm.

[0037] In one of the above examples, the refractory sagger may be sintered from a raw material containing petalite.

[0038] At this time, the refractory sagger may be sintered from raw materials in which a discontinuous phase aggregate including at least one selected from spinel, corundum, mullite, cordierite, quartz and zircon is dispersed in a continuous phase masterbatch matrix including petalite.

[0039] In addition, the content of petalite in the above raw material may be 20 wt % to 40 wt %.

[0040] In addition, the refractory sagger may include 20 wt % to 50 wt % of a solid solution containing β-spodumene and SiO 2 .

[0041] Effects of the Invention

[0042] The refractory sagger for calcining a precursor material according to various embodiments of the present specification includes a ceramic material having sufficient heat resistance, and thus has an advantage of being repeatedly used in a process of calcining a precursor material of an inorganic compound.

[0043] In addition, the refractory sagger for calcining the precursor material according to various embodiments of the present specification includes a protective layer with low reactivity with lithium in at least a portion of the internal space in which the precursor material is loaded, thereby minimizing the reaction of the ceramic material with the lithium-containing raw material to generate Li x -(Al / Si) y -O z Therefore, compared with the prior art, the service life of the refractory sagger is extended.

[0044] In addition, the refractory sagger for calcining the precursor material has sufficient strength, and the amount of stress generated under repeated temperature changes is also small, thereby minimizing the generation of cracks in the refractory sagger, and thus has the advantage of excellent durability.

[0045] In addition to the above-described effects, specific effects of the present invention will be described while explaining specific details for implementing the present invention. DETAILED DESCRIPTION

[0046] Specific terms are defined herein for ease of understanding. Unless specifically defined herein, scientific terms and technical terms used herein should have the meanings commonly understood by those skilled in the art. In addition, it should be understood that as used herein, unless the context clearly indicates otherwise, the singular form is intended to include the plural form, and vice versa.

[0047] Additionally, unless otherwise specified herein, each property may be measured at 25°C and 1 bar.

[0048] Hereinafter, the refractory sagger for calcining a precursor material according to the present specification will be described in more detail.

[0049] Refractory sagger protective layer

[0050] According to one aspect of the present invention, a refractory sagger for calcining precursor materials is provided, which is a refractory sagger having a space for loading the precursor materials on the inside, and a protective layer having a spinel content of more than 50 wt% is formed on at least a portion of the inner surface of the refractory sagger for loading the precursor materials.

[0051] A refractory sagger is a refractory container for calcining precursor materials to produce desired products while preventing direct contact with flames, fumes, etc.

[0052] Therefore, the shape of the refractory sagger is not limited to a prism, a cylinder, an elliptical cylinder, etc., and it can be used in various ways according to the purpose as long as it includes a space inside which the precursor material can be placed.

[0053] Examples of the above-mentioned precursor material include lithium-based oxides and the like for preparing a positive electrode active material.

[0054] Generally, a precursor material for preparing a positive electrode active material contains lithium and at least one of cobalt, nickel, manganese and iron, and is calcined to form a lithium-based composite oxide, which can be used as a positive electrode active material.

[0055] During the calcination process, lithium infiltrates into the refractory sagger and reacts, and as a result, there is a problem that the components of the refractory sagger deteriorate and peel off.

[0056] In order to minimize the manufacturing cost of the calcined final product, the refractory sagger must be reused, but the refractory sagger that has been delaminated may reduce product properties and thus cannot or is difficult to reuse.

[0057] According to one aspect of the present specification, such a problem can be improved by forming a protective layer having low reactivity with lithium on at least a portion of the inner surface of the space inside the refractory sagger in which the precursor material is placed.

[0058] That is, at least a portion of the refractory sagger may have a dual structure consisting of a main body and a protective layer.

[0059] As an example of such a refractory sagger, a protective layer may be formed on the bottom surface of the inner space of the refractory sagger into which lithium is more easily permeated due to gravity, but the present invention is not limited thereto.

[0060] Since the sagger must be repeatedly subjected to a high-temperature calcination process, it may be made of a ceramic material having a high melting point.

[0061] Ceramic materials are materials composed of compounds formed by combining metal elements such as silicon (Si), aluminum (Al), titanium (Ti), zirconium (Zr), and magnesium (Mg) with non-metal or metalloid elements such as oxygen, carbon, and nitrogen through high-temperature heat treatment.

[0062] For example, the ceramic material constituting the refractory sagger for calcining the precursor material of the present application may include Al2O3, MgO, SiO2, K2O, ZrO, ZrO2, CaO and Fe x O y The various materials known as the materials constituting the refractory sagger are as follows.

[0063] In addition to the chemical composition represented by the above formula, the properties of ceramic materials may also vary depending on the morphology, ie, the type of mineral phase, in which they are formed.

[0064] Examples of mineral phases of ceramic materials that can be used for refractory saggers in the present specification include spinel, corundum, mullite, cordierite, spodumene, zircon, quartz, petalite, eucryptite, lithium disilicate, lithium metasilicate, forsterite, magnesium metasilicate, alumina, silicate, and the like.

[0065] The general forms of these materials are described below, but the present invention is not limited thereto. For example, the coefficient of thermal expansion of each component is an example value measured in the temperature range of 25°C to 800°C.

[0066] Spinel is an isometric mineral represented by MgO·Al2O3, for example, having a -6 / ℃ thermal expansion coefficient.

[0067] Corundum is a hexagonal mineral represented by Al2O3, for example, which can have a crystal structure of about 7.26×10 -6 / ℃ thermal expansion coefficient.

[0068] Mullite is a tetragonal mineral represented by 3Al2O3·2SiO2, and may have a relative humidity of about 5.84×10 -6 / ℃ thermal expansion coefficient.

[0069] Cordierite is a tetragonal mineral represented by 2MgO·2Al2O3·5SiO2, and may have a relative humidity of about 1.76×10 -6 / ℃ thermal expansion coefficient.

[0070] Spodumene is represented by Li2O·Al2O3·nSiO2 and is divided into monoclinic α-spodumene and tetragonal β-spodumene according to the production temperature. For example, it can have a carbon content of about 0.44×10 -6 / ℃ thermal expansion coefficient.

[0071] Zircon is a tetragonal phase represented by ZrO2·SiO2, and may have a relative humidity of about 2.03×10 -6 / ℃ thermal expansion coefficient.

[0072] Quartz is a hexagonal phase represented by SiO2, and may have a crystal structure of about 7.64×10 -6 / ℃ thermal expansion coefficient.

[0073] These minerals react with lithium to degrade into phases of Li4SiO4, β-LiAlO2, γ-LiAlO2, MgO, etc.

[0074] These degraded phases reduce the bonding strength between components and become the cause of refractory sagger peeling.

[0075] Specifically, when the precursor material is calcined using the refractory sagger, lithium from the lithium-containing raw material (LiOH, etc.) contained in the precursor material penetrates into the refractory sagger, so that the lithium x -(Al / Si) y -O z Impurities represented by the composition of the above-mentioned refractory sagger are deposited on the inner side.

[0076] With the repeated use of the refractory sagger, an impurity layer (or referred to as a deteriorated layer) having a predetermined thickness may be generated on the inner side, especially the bottom surface, of the refractory sagger.

[0077] If cracks appear in the impurity layer generated as described above or the impurity layer peels off from the refractory sagger, not only is there a risk that the quality of firing using the refractory sagger will be drastically reduced, but there is also a possibility that the refractory sagger cannot be used.

[0078] Therefore, in order to inhibit the lithium in the lithium-containing raw material (LiOH, etc.) contained in the above-mentioned precursor material from penetrating into the above-mentioned refractory crucible and forming an impurity reaction, it is preferred that the masterbatch forming the protective layer of the internal space of the refractory crucible loaded with the above-mentioned precursor material does not contain SiO2, or the proportion of the SiO2-containing phase in the masterbatch does not exceed half.

[0079] Therefore, the reactivity of the protective layer master batch to lithium may be lower than the reactivity of the protective layer aggregate to lithium.

[0080] Among the above components, the reactivity to lithium gradually increases in the order of spinel, mullite, cordierite, zircon, quartz, spodumene and corundum. Therefore, the peeling of the refractory sagger can be suppressed by adjusting the composition of the above protective layer.

[0081] In the present specification, spinel is the ceramic material least reactive to lithium for the refractory sagger, and the protective layer can improve the problem of easy peeling of the refractory sagger when the calcination process is repeated multiple times by including more than 50 wt % of spinel.

[0082] For example, the protective layer may contain more than 50 wt % of spinel, preferably, 50 wt % to 85 wt % of spinel, so as to improve the anti-stripping property of the refractory sagger.

[0083] In one example, in addition to more than 50 wt % of spinel, the protective layer may further include at least one selected from the group consisting of corundum, mullite, petalite, spodumene, cordierite, quartz, and zircon.

[0084] As described above, the protective layer may contain various components in addition to spinel, thereby minimizing the difference in thermal expansion coefficient between the refractory sagger body and the protective layer.

[0085] For example, if the thermal expansion coefficient of the refractory sagger body is 4.0×10 -6 / ℃, the thermal expansion coefficient can be 6.72×10 -6 / ℃ spinel and a component with a relatively low thermal expansion coefficient to form a protective layer.

[0086] If the difference in thermal expansion coefficient between the refractory sagger body and the protective layer formed thereon is large, cracks may be generated due to stress formed in the protective layer or the body during repeated calcination processes, thereby reducing the service life of the refractory sagger.

[0087] Therefore, the difference in thermal expansion coefficient between the protective layer and the main body can be 1.5×10 -6 / ℃ or less, preferably, it can be 1.0×10 -6 / °C or less, more preferably, 0.5×10 -6The following, but the present invention is not limited thereto.

[0088] In addition, the calcination efficiency can be improved by adjusting the composition of the protective layer to increase the thermal conductivity.

[0089] The sagger is heat-treated in a kiln or the like in a state where the precursor material is loaded, and therefore, if the protective layer in direct contact with the precursor material has a high thermal conductivity, heat can be more efficiently transferred to the precursor material.

[0090] On the other hand, in addition to the deterioration of the refractory sagger due to the penetration and reaction of lithium, the impact applied by the pressurization during the charging of the precursor material, the volume change during the sintering process, etc. may also reduce the service life of the refractory sagger.

[0091] Therefore, in another example, the mechanical strength of the refractory sagger can be improved by adjusting the composition of the protective layer.

[0092] In addition, other components besides spinel added to the protective layer can also be used to enhance the bonding force between the protective layer and the refractory sagger body.

[0093] As one of the multiple examples, the corundum content of the protective layer may be less than 25 wt %. When corundum is included, the content may be 5 wt % to 25 wt %, and preferably, 7.5 wt % to 20 wt %.

[0094] When the protective layer contains corundum, if the content thereof exceeds 25% by weight, the anti-peeling property of the refractory sagger may be reduced.

[0095] In another example, the protective layer may be a spinel continuous phase masterbatch matrix in which a discontinuous phase aggregate including at least one selected from the group consisting of corundum, mullite, petalite, spodumene, cordierite, quartz and zircon is dispersed.

[0096] Since the components constituting the refractory sagger with a smaller average particle size have a higher reactivity with lithium during the calcination of the precursor material, the protective layer can use spinel as a masterbatch, while the other components can be applied as aggregates with a larger average particle size.

[0097] When the protective layer has the above-mentioned form, the spaces between the aggregates with larger particle sizes may be filled with masterbatch in the form of fine powder.

[0098] As a result, when the sagger is sintered, the master batch and the aggregate of the protective layer can be combined with each other or separately to form a dense structure.

[0099] This dense structure can suppress the peeling phenomenon caused by the penetration and reaction of lithium and impart excellent impact resistance to the protective layer, thereby preventing the refractory sagger from being damaged when the precursor material is calcined.

[0100] As described above, the protective layer of the refractory sagger for calcining precursor materials according to the present specification contains aggregates and master batches having different average particle size ranges, thereby reducing the porosity of the protective layer and increasing the specific gravity.

[0101] When the porosity of the protective layer is reduced, the possibility of lithium derived from the lithium-containing raw material included in the precursor material penetrating into the refractory sagger during calcination of the precursor material using the refractory sagger is also reduced.

[0102] As an example of a protective layer composition capable of forming a dense structure, the spinel masterbatch having an average particle size of 0.5 μm to 25 μm and the aggregate having an average particle size of 150 μm to 900 μm may be used, but is not limited thereto.

[0103] The preparation method of particles having the above-mentioned particle size is not limited. For example, evaporation-condensation method, chemical vapor deposition method, gas phase thermal decomposition method, gas phase reduction method, coprecipitation method, hydrolysis method, spray drying method, freeze drying method, thermal decomposition method, reduction method, solid phase reaction method, sublimation method and solution method can be used according to the type of raw materials and the required properties.

[0104] In one example, the spinel masterbatch with a smaller average particle size can be prepared by micronizing the raw materials through various pulverization methods.

[0105] For example, the raw material can be pulverized by using a pulverizing method such as a ball mill, a pebble mill, a rod mill, a roller mill, a colloid mill, an impact mill, and a jet mill.

[0106] In one embodiment, if the thickness of the protective layer is too thin or too thick, its anti-peeling performance may be reduced.

[0107] Although the specific mechanism has not yet been clarified, if the thickness of the above-mentioned protective layer is too thin, lithium may penetrate through the protective layer into the refractory sagger body, resulting in a decrease in the bonding strength between the above-mentioned protective layer and the body, thereby causing peeling.

[0108] On the contrary, if the thickness of the protective layer is too thick, the protective layer may not be fully sintered, the formation of a dense structure is insufficient, and lithium is more easily penetrated, thereby causing the occurrence of peeling.

[0109] Therefore, preferably, the thickness of the protective layer may be 2.5 mm to 4.0 mm.

[0110] Refractory sagger body

[0111] According to an embodiment of the present specification, the refractory sagger body may be made of a ceramic material as described above.

[0112] Examples of the mineral phase of the aforementioned ceramic material include spinel, corundum, mullite, cordierite, spodumene, zircon, quartz, petalite, eucryptite, lithium pyrosilicate, lithium metasilicate, forsterite, magnesium metasilicate, alumina, silicates, and the like.

[0113] Even if these materials have similar chemical compositions, the rate of volume change due to temperature changes may be different.

[0114] In the process of calcining precursor materials using refractory saggers, in addition to the peeling caused by the penetration and reaction of lithium, cracks caused by repeated thermal shock are also one of the factors that determine the service life of the refractory saggers.

[0115] For example, when the precursor material is calcined, it expands and exerts pressure on the refractory sagger, especially on its wall surface, which may cause cracks.

[0116] In addition, cracks may also occur due to the difference in thermal expansion coefficient between the protective layer and the main body.

[0117] As another example, changes in the volume of the components in the refractory sagger body composition may also be a cause of cracks.

[0118] As a means for minimizing the occurrence of the above cracks, a refractory sagger formed by sintering a raw material containing petalite may be used as the above refractory sagger.

[0119] Specifically, the main body of the refractory sagger may include a spodumene phase, in particular, β-spodumene, sintered from a raw material containing petalite.

[0120] The spodumene phase is easily affected by the penetration and reaction of lithium, so if used alone, the refractory sagger may peel off when the calcination reaction of the precursor material is repeated. However, as described above, the reduction in the service life of the refractory sagger caused by peeling can be suppressed by forming a protective layer with excellent resistance to lithium reactivity.

[0121] In addition to petalite, the above-mentioned refractory sagger body can further include spinel, corundum, mullite, cordierite, spodumene, zircon, quartz, eucryptite, lithium disilicate, lithium metasilicate, forsterite, magnesium metasilicate, alumina, silicate and other components, so that it can be adjusted to have a thermal expansion coefficient at a similar level to the above-mentioned protective layer.

[0122] The difference in thermal expansion coefficient between the refractory sagger body and the protective layer can be adjusted to 1.5×10 -6 / °C or less, preferably 1.0×10 -6 / °C or less, more preferably 0.5×10 -6 / ℃ or below, but not limited to this.

[0123] On the other hand, the refractory sagger body may be composed of aggregates and master batches each having a specific thermal expansion coefficient.

[0124] The above-mentioned refractory sagger is mainly used under high-temperature calcination conditions. If the ceramic material used as aggregate and masterbatch has a large thermal expansion coefficient, the volume change rate before and after calcination may be too large, thereby causing cracks in the above-mentioned refractory sagger.

[0125] Therefore, at least one of the aggregate and the master batch constituting the refractory sagger body, or at least one of the ceramic materials used as the aggregate and the master batch, preferably has a relatively small thermal expansion coefficient.

[0126] The thermal expansion coefficients of these masterbatches or aggregates may vary depending on the composition of the refractory sagger and the absolute magnitude of the thermal expansion coefficient.

[0127] For example, in one example of the present invention, the refractory sagger may be formed by using a material having a thermal expansion coefficient of an aggregate relatively lower than a thermal expansion coefficient of a master batch.

[0128] The above-mentioned aggregate exists in the form of a discontinuous phase in the continuous phase matrix composed of the above-mentioned masterbatch. Therefore, in this form of refractory sagger, if the thermal expansion coefficient of the above-mentioned aggregate is large, some areas of the refractory sagger may locally undergo volume changes, thereby forming stress.

[0129] Generally speaking, a ceramic material including SiO 2 in its crystal structure may have a smaller thermal expansion coefficient than a ceramic material not including SiO 2 in its crystal structure.

[0130] However, as mentioned above, SiO2 may react with lithium-containing raw materials to form by-products, so oxides containing SiO2 in the crystal structure are more suitable as aggregates rather than masterbatches.

[0131] In the above-mentioned refractory sagger, among the components other than petalite, a ceramic material containing SiO2 in its crystal structure may be used as the above-mentioned aggregate.

[0132] Furthermore, if the content of the ceramic material containing SiO2 in the crystal structure of the aggregate increases, the reactivity with the lithium-containing raw material may also increase.

[0133] Therefore, the generation of by-products can be suppressed by adjusting the content of the ceramic material including SiO2 in the above-mentioned aggregate to an appropriate range, or adjusting the content of the above-mentioned aggregate relative to the above-mentioned master batch to an appropriate range.

[0134] On the other hand, in another example of the present invention, the refractory sagger may be formed by using a material having a thermal expansion coefficient of a master batch relatively smaller than a thermal expansion coefficient of an aggregate.

[0135] In the refractory sagger, by using the masterbatch having a smaller high-temperature volume change rate, the phenomenon of stress concentration in the continuous phase matrix is ​​alleviated, thereby reducing the occurrence of cracks in the refractory sagger.

[0136] This type of sagger has a high possibility of forming a deterioration layer due to the penetration and reaction of lithium, and therefore it is necessary to form a protective layer as described above.

[0137] That is, when a refractory sagger is manufactured using petalite containing SiO 2 in its crystal structure as a master batch, it is necessary to form a protective layer having low reactivity to lithium in order to improve the peeling resistance as described above.

[0138] In one embodiment of the present specification, the refractory sagger may be sintered from raw materials comprising a continuous phase masterbatch matrix containing petalite in which at least one discontinuous phase aggregate selected from spinel, corundum, mullite, cordierite, quartz and zircon is dispersed.

[0139] As described above, the refractory sagger body for calcining a precursor material according to the present specification can reduce the porosity of the refractory sagger body and increase its specific gravity by mixing aggregates and masterbatches having different average particle size ranges.

[0140] When the porosity of the refractory sagger body is reduced, when the refractory sagger is used to calcine a precursor material, the possibility that part of the lithium from the lithium-containing raw material contained in the precursor material penetrates into the refractory sagger body through the protective layer is reduced.

[0141] As a result, even when using a petalite raw material having high reactivity to lithium, the reduction in the service life of the refractory sagger caused by the exfoliation can be minimized.

[0142] In addition, as the specific gravity of the refractory sagger body increases, sufficient strength can be imparted to withstand the pressure applied to the inner wall of the refractory sagger when the precursor material is loaded into the refractory sagger and then pressed.

[0143] In one example, the average particle size of the raw material forming the continuous phase masterbatch matrix may be 0.5 μm to 25 μm, and the average particle size of the raw material forming the discontinuous phase aggregate may be 150 μm to 900 μm, but is not limited thereto.

[0144] If the raw material of the continuous phase masterbatch includes petalite, the occurrence of cracks due to the volume change of the refractory sagger body at high temperature can be minimized.

[0145] Other components with relatively large volume change rates may be mixed with components that compensate for the volume change rate.

[0146] For example, a component that expands in volume at the temperature at which the calcining process is performed may be mixed with a component that shrinks in volume, thereby minimizing the overall volume change rate.

[0147] On the other hand, unlike the spodumene phase formed of α-spodumene, the spodumene phase formed of petalite may have a low volume expansion rate.

[0148] Specifically, petalite can be transformed into a solid solution containing β-spodumene and SiO2 during the sintering process of the refractory sagger.

[0149] The solid solution has a lower volume change rate within the temperature range of calcining the precursor material, thereby reducing the problem of cracks in the refractory sagger caused by stress caused by volume change.

[0150] Specifically, the volume change rate of the spodumene phase derived from petalite in the range of 25°C to 1200°C is 0.020% or less, while the volume change rate of the structure derived from α-spodumene in the range of 25°C to 1200°C may exceed 0.1%.

[0151] In the above raw materials, the content of petalite may be 20 wt % to 40 wt %, preferably 25 wt % to 35 wt %, and more preferably 30 wt % to 33 wt %.

[0152] When the content of petalite in the raw material meets the above range, the crack resistance of the refractory sagger can be significantly improved.

[0153] In addition, the refractory sagger may include 20 wt % to 50 wt % of a solid solution containing β-spodumene and SiO 2 .

[0154] The solid solution can be formed by sintering petalite raw material, but a solid solution containing β-spodumene and SiO2 can also be formed by other means, thereby improving the crack resistance of the refractory sagger.

[0155] In the above solid solution, the molar ratio of Li2O·Al2O3 to SiO2 may be 1:7 to 1:9. If the molar ratio exceeds the above range, the volume change rate at high temperature increases, resulting in reduced crack resistance of the refractory sagger.

[0156] Method for manufacturing refractory sagger

[0157] The refractory sagger of the present specification can be manufactured by mixing raw materials of ceramic materials, molding them into a predetermined shape, and then heat-treating them.

[0158] The average particle size of the masterbatch in the raw material may be 0.5 μm to 25 μm, and the average particle size of the aggregate may be 150 μm to 900 μm, but are not limited thereto.

[0159] The preparation method of particles having the above-mentioned particle size is not limited. For example, evaporation-condensation method, chemical vapor deposition method, gas phase thermal decomposition method, gas phase reduction method, coprecipitation method, hydrolysis method, spray drying method, freeze drying method, thermal decomposition method, reduction method, solid phase reaction method, sublimation method and solution method can be used according to the type of raw materials and the required properties.

[0160] The masterbatch with a small average particle size can be used after being micronized by various pulverization methods, for example, ball milling, pebble milling, rod milling, roller milling, colloid milling, impact milling, and air flow milling.

[0161] Here, the raw materials may be mixed by a dry mixing method in which powders are directly mixed, or by a wet mixing method in which powders are made into slurry and then mixed. There is no limitation as long as the raw materials can be mixed uniformly.

[0162] Furthermore, in order to facilitate molding, the raw materials may be mixed in a form further containing an organic binder such as a binder.

[0163] In this case, the type of the organic binder is not limited as long as it can be removed in a high-temperature heat treatment process.

[0164] At this time, the amount of the organic binder used is not limited as long as it can provide a desired level of bonding strength within a range that does not adversely affect the physical properties of the sagger after removal in the heat treatment process.

[0165] On the other hand, the mixed raw materials can be formed into a predetermined shape to produce a refractory sagger in the above-mentioned form.

[0166] For example, it can be molded into a columnar shape having an inner space by pressing.

[0167] In one example, the protective layer of the inner space of the refractory sagger may be formed by molding a refractory sagger body raw material and a protective layer raw material together.

[0168] For example, the refractory sagger body raw material and the protective layer raw material can be stacked and then pressed, or the refractory sagger body can be pressed first and then the protective layer raw material can be stacked, or the refractory sagger body can be pressed first and then the protective layer raw material can be coated, or the refractory sagger body can be pressed first and then the protective layer raw material can be stacked and then pressed, etc. The method is not limited.

[0169] The formed refractory sagger raw material can be sintered by heat treatment to manufacture the refractory sagger.

[0170] At this time, the heat treatment temperature of the raw material can be adjusted according to the composition of the refractory sagger raw material, for example, it can be 1150°C to 1800°C.

[0171] The sintering temperature will vary depending on the chemical composition or phase of the raw materials, and phase changes may be caused depending on the sintering temperature.

[0172] Therefore, the above heat treatment temperature varies depending on the desired composition and phase of the final refractory sagger.

[0173] The above heat treatment may be performed once or multiple times.

[0174] When the above heat treatment is performed multiple times, the phase of the refractory sagger can be adjusted by changing the temperature and time of each step.

[0175] The refractory sagger manufactured by such heat treatment may be used directly, or may be used after further forming a coating or the like.

[0176] Hereinafter, the present invention will be described in more detail by way of examples. However, these examples are only intended to illustrate the present invention, and the scope of the present invention should not be construed as being limited by these examples.

[0177] Experimental Example 1. Evaluation of crack resistance characteristics based on the composition of the refractory sagger body

[0178] In order to evaluate crack resistance characteristics according to the main composition, the raw materials were hydraulically pressed and then sintered at 1250° C. to produce refractory saggers having the compositions shown in Table 1 below.

[0179] Here, in Comparative Example 2, α-spodumene was added as a masterbatch, and in Examples 1 and 2, petalite was added as a masterbatch.

[0180] α-spodumene (Li2O·Al2O3·4SiO2; monoclinic system) and petalite (Li2O·Al2O3·8SiO2) added as raw materials are transformed into β-spodumene (Li2O·Al2O3·4SiO2; tetragonal system) during the sintering process.

[0181] Table 1

[0182] Classification Spinel Iolite Spodumene Corundum Mullite Zircon quartz other Comparative Example 1 45 35 - 12.5 5 2.5 - - Comparative Example 2 50 - 32.5 7.5 7.5 - - 2.5 Example 1 57.5 - 25 7.5 7.5 - - 2.5 Example 2 49 - 30 6.5 6.5 - 3 5

[0183] (Unit: weight %)

[0184] After the same type of lithium composite oxide was placed in each refractory sagger, the temperature was raised to 780° C. at a rate of 2° C. per minute while maintaining an O 2 atmosphere, and calcination was performed for 12 hours.

[0185] By repeatedly performing this calcination process, the last calcination number before the sagger could not be used due to cracks was determined as its anti-crack life and is shown in Table 2 below.

[0186] Table 2

[0187] Classification Comparative Example 1 Comparative Example 2 Example 1 Example 2 Anti-crack life (times) 4 5 10 15

[0188] Referring to Table 2, the crack resistance of Examples 1 and 2 in which petalite is added when manufacturing the refractory box body is better than that of the comparative example.

[0189] In particular, although the spodumene phase exists in Comparative Example 2, it can be confirmed that the crack resistance life is similar to that of Comparative Example 1, unlike Examples 1 and 2 which are excellent in crack resistance.

[0190] Although the mechanism is unclear, it is expected that petalite with a high SiO2 content has excellent crack resistance because its volume change at high temperatures is minimized due to the formation of a solid solution between β-spodumene and SiO2.

[0191] Experimental Example 2. Evaluation of Lithium Reactivity of Raw Materials

[0192] LiOH melts at 450°C and can be lithiated as shown in the following reaction formula.

[0193] Therefore, the lithium reactivity of each raw material can be confirmed by mixing the components of the refractory sagger with LiOH and then calcining the mixture at 450°C.

[0194] [Reaction formula]

[0195] 2LiOH→Li2O+H2O

[0196] Spinel, mullite, cordierite, zircon, quartz, petalite and corundum were sintered at 1250 °C and then mixed with LiOH in a weight ratio of 1:4.

[0197] The mixture was heated to 450° C. at a rate of 2.5° C. per minute and calcined for 5 hours, and then the lithium reactivity of the raw material was evaluated by XRD phase analysis and is shown in Table 3 below.

[0198] Table 3

[0199]

[0200] (Unit: weight %)

[0201] The lithium reactivity was evaluated by the ratio of LiOH to Li4SiO4, β-LiAlO2, γ-LiAlO2, MgO, etc. after thermal decomposition, and the results confirmed that spinel had the lowest reactivity.

[0202] After preparing corundum with the highest lithium reactivity having different average particle sizes, it was mixed with LiOH at a weight ratio of 1:4.

[0203] The mixture was heated to 450° C. at a rate of 2.5° C. per minute and calcined for 1 hour, and then the lithium reactivity of the corundum according to the different average particle sizes was evaluated by XRD phase analysis and is shown in Table 4 below.

[0204] Table 4

[0205] Average particle size (μm) 4.00 9.47 12.48 Corundum (weight %) 32.1 41.3 41.8 <![CDATA[β-LiAlO2 (wt%)]]> 50.4 40.8 31.6 <![CDATA[γ-LiAlO2 (wt%)]]> 17.5 17.9 26.6

[0206] Referring to Table 4, it can be confirmed that the lithium reactivity decreases as the average particle size of the raw material increases. In addition, when particles with a particle size ranging from 150 μm to 900 μm and larger than that of corundum in Table 4 were used and calcined under the same conditions, no lithium reaction was observed.

[0207] Based on the above results, it can be inferred that using a raw material with relatively low lithium reactivity as a masterbatch of fine powder and using a raw material with high lithium reactivity as an aggregate with a larger average particle size can extend the service life of the refractory sagger.

[0208] Experimental Example 3. Evaluation of the anti-stripping properties of the refractory sagger protective layer

[0209] In Example 2, raw materials were stacked in two layers on the bottom surface of the inner space of the refractory sagger in which the positive electrode precursor was loaded to form a protective layer having the composition shown in Table 5 below, and then hydraulic press molding was performed and sintered at 1250° C. to manufacture a refractory sagger.

[0210] Table 5

[0211]

[0212] (Unit: weight %)

[0213] After the same type of lithium composite oxide was placed in each refractory sagger, the temperature was raised to 780° C. at a rate of 2° C. per minute while maintaining an O 2 atmosphere, and calcination was performed for 12 hours.

[0214] By repeatedly performing the above calcination process, the last calcination number before the sagger cannot be used due to bottom peeling is determined as its peeling resistance life, and is shown in Table 6 below.

[0215] Table 6

[0216] Classification Comparative Example 1 Example 3 Example 4 Example 5 Peeling resistance life (times) 4 8 8 8

[0217] Referring to the results of Experimental Example 2 and Table 6, in Comparative Example 1 without a separate protective layer, due to the penetration and reaction of lithium, after 5 calcination processes, 14.36% of the entire bottom surface area peeled off, making the refractory sagger unusable. In the embodiments in which a protective layer with a spinel content of 50 wt% or more was formed, it was confirmed that the peeling resistance life was more than 8 times.

[0218] This shows that a refractory sagger having excellent peeling resistance can be manufactured by constructing a double-layer structure in which a protective layer with low lithium reactivity is formed on the bottom surface of the refractory sagger in contact with the charged lithium composite oxide.

[0219] In the refractory sagger of Example 3, the thickness of the protective layer was changed and the peeling resistance life was measured. The results are shown in Table 7 below.

[0220] Table 7

[0221]

[0222] With reference to Table 7, it can be confirmed that when the thickness of the protective layer is too thin or too thick, the peeling resistance life is reduced.

[0223] Although the embodiments of the present invention are described above, those skilled in the art will understand that various modifications and changes can be made to the present invention by adding, modifying, deleting, increasing, etc., without departing from the scope of the idea of ​​the present invention as described in the claims, and these also fall within the scope of the rights of the present invention.

Claims

1. A refractory sagger for calcining a precursor material, which is a refractory sagger having a space for loading the precursor material inside, characterized in that: A protective layer having a spinel content of 50 wt % or more is formed on at least a portion of the inner surface of the refractory sagger on which the precursor material is placed.

2. The refractory sagger for calcining precursor materials according to claim 1, characterized in that: The protective layer further comprises at least one selected from the group consisting of corundum, mullite, petalite, spodumene, cordierite, quartz and zircon.

3. The refractory sagger for calcining precursor materials according to claim 2, characterized in that: The protective layer has a corundum content of 25% by weight or less.

4. The refractory sagger for calcining precursor materials according to claim 2, characterized in that: The protective layer comprises a spinel continuous phase masterbatch matrix in which discontinuous phase aggregates including at least one selected from the group consisting of corundum, mullite, petalite, spodumene, cordierite, quartz and zircon are dispersed.

5. The refractory sagger for calcining precursor materials according to claim 4, characterized in that: The average particle size of the spinel masterbatch is 0.5 μm to 25 μm. The average particle size of the above-mentioned aggregate is 150 μm to 900 μm.

6. The refractory sagger for calcining precursor materials according to claim 1, characterized in that: The thickness of the protective layer is 2.5 mm to 4.0 mm.

7. The refractory sagger for calcining precursor materials according to any one of claims 1 to 6, characterized in that: The refractory sagger is sintered from raw materials containing petalite.

8. The refractory sagger for calcining precursor materials according to claim 7, characterized in that: The refractory sagger is sintered from raw materials in which a discontinuous phase aggregate including at least one selected from spinel, corundum, mullite, cordierite, quartz and zircon is dispersed in a continuous phase masterbatch matrix including petalite.

9. The refractory sagger for calcining precursor materials according to claim 7, characterized in that: The content of petalite in the above raw material is 20 wt % to 40 wt %.

10. The refractory sagger for calcining precursor materials according to claim 7, characterized in that: The refractory sagger includes 20 wt % to 50 wt % of a solid solution containing β-spodumene and SiO2.

Citation Information

Patent Citations

  • Refractory material for sintering lithium secondary battery cathode active material and its manufacturing method

    KR1020200058383A

  • Ceramic coating sagger for manufacturing lithium ion anode active material and manufacturing method thereof

    CN103884190A

  • Sagger for positive electrode material of lithium ion battery and preparation method of sagger

    CN114195533A

  • Tool for burning

    JP2010223468A

  • Lightweight kiln-utensil, and method of producing the same

    JP2022070459A